Causal relationship between energy consumption, economic growth, and CO2 emissions in the Philippines - Ibañez, Jessa A. (College of Engineering, University of the Philippines Diliman, 2019)
The study examined the causal relationship between energy consumption, economic growth, and CO2 emissions in the Philippines in a multivariate model using time series data from 1965-2017. The study employed Toda and Yamamoto procedure to test causality directions between the variables and generalized impulse response function to analyze how a change in variable affects the others. Empirical findings suggest that there is bidirectional relationship running from income to energy consumption, and unidirectional relationship running from CO2 emissions to energy consumption. Results also suggest that economic growth may help CO2 reduction in the long run but CO2 reduction may counteract with economic growth as long as the country continues to rely on fossil fuels as its main energy source. Also, the Philippines can implement energy conservation policies without limiting its economic growth and that energy consumption can be increased without increasing CO2 emissions